Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/cid.12035
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Implants Placed Simultaneously with Sinus Membrane Elevation in the Posterior Atrophic Maxilla: A Two‐Year Follow‐Up Study on 10 Patients

Abstract: Within the limits of this case series report, it is concluded that maxillary sinus membrane elevation with simultaneous placement and immediate loading of implants without the use of any additional grafting material shows predictable results after 2 years of functional loading. Moreover, evidence of intrasinus bone formation around the implants was found in all patients. Further studies are needed to study the influence of immediate loading on the mineralization of bone forming at dental implant sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…An experimental animal study confirmed the results by histological means and could verify bone formation and implant integration . Several other authors have demonstrated similar and predictable results, even in cases with a reduced residual bone height . However, the mechanisms and, for instance, the role of the sinus membrane (Schnederian membrane) for bone formation following sinus elevation are not well understood.…”
Section: Introductionsupporting
confidence: 65%
“…An experimental animal study confirmed the results by histological means and could verify bone formation and implant integration . Several other authors have demonstrated similar and predictable results, even in cases with a reduced residual bone height . However, the mechanisms and, for instance, the role of the sinus membrane (Schnederian membrane) for bone formation following sinus elevation are not well understood.…”
Section: Introductionsupporting
confidence: 65%
“…When it comes to long‐term predictability, several papers have documented the long‐term reliability of dental implants in the treatment of edentulism in both maxilla and mandible; in all these studies, implants were used with either a one or two‐stage surgical approach but always with a delayed loading protocol. Since the early 1990s when Schnitman and colleagues first documented the reliability of the immediate loading of implants in the fully edentulous mandible, this concept has been further documented and reported to also be feasible and predictable in cases of maxillary partial and total edentulism . Predictable results are believed to depend on good initial implant stability, controlled loading conditions, and an osseo‐conductive implant surface …”
Section: Introductionmentioning
confidence: 99%
“…Bone formation by sinus membrane elevation has been proven in several studies (Lundgren et al, 2004(Lundgren et al, , 2008Palma et al, 2006;Cricchio et al, 2011aCricchio et al, , 2011bCricchio et al, , 2014Jungner et al, 2014).…”
Section: Resultsmentioning
confidence: 96%